2020
DOI: 10.1126/scitranslmed.aaw3703
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infections drive heterogeneity in human type 2 and regulatory cells

Abstract: Helminth infections induce strong type 2 and regulatory responses, but the degree of heterogeneity of such cells is not well characterized. Using mass cytometry, we profiled these cells in Europeans and Indonesians not exposed to helminths and in Indonesians residing in rural areas infected with soil-transmitted helminths. To assign immune alteration to helminth infection, the profiling was performed before and 1 year after deworming. Very distinct signatures were found in Europeans and Indonesians, showing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…However, there is increasing evidence suggesting that interpopulation differences in immunological profiles are driven by non-inheritable environmental factors such as prior and current infection status which may typically be vastly different between rural vs. urban living (59, 68, 69). For example, rural African populations express a superior immune activated state, larger memory pool and Th2 polarization as compared to urban Africans (64) and Indonesians from a non-endemic urban setting showed a similar immune profile to European subjects yet markedly differed from Indonesians from an endemic rural area (59). More so, a type 2 immune profile comprising of Th2 cells, IL-4, IL-5, and IL-13 cytokines is typical of schistosomiasis high-exposure endemic populations (70).…”
Section: Population Differences In Immune Profile Affecting Vaccine Rmentioning
confidence: 99%
“…However, there is increasing evidence suggesting that interpopulation differences in immunological profiles are driven by non-inheritable environmental factors such as prior and current infection status which may typically be vastly different between rural vs. urban living (59, 68, 69). For example, rural African populations express a superior immune activated state, larger memory pool and Th2 polarization as compared to urban Africans (64) and Indonesians from a non-endemic urban setting showed a similar immune profile to European subjects yet markedly differed from Indonesians from an endemic rural area (59). More so, a type 2 immune profile comprising of Th2 cells, IL-4, IL-5, and IL-13 cytokines is typical of schistosomiasis high-exposure endemic populations (70).…”
Section: Population Differences In Immune Profile Affecting Vaccine Rmentioning
confidence: 99%
“…The induction of GATA3 + Th2 cells is a prototypical host immune response to helminth infections and the Th1/Th2 ratio is supposed to be a crucial point in assessing the effects of helminth therapy on Th1-driven inflammatory conditions. A recent study has addressed the heterogeneity of human Th2 cells during helminth infection in more detail [ 43 ]. They describe a decrease in a particular subset of CD27 − CD161 + Th2 subset after deworming of helminth-infected individuals, which as a more pathogenic Th2 subset with enhanced effector functions potentially exert specific regulatory functions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has addressed the heterogeneity of human Th2 cells during helminth infection in more detail [ 43 ]. They describe a decrease in a particular subset of CD27 − CD161 + Th2 subset after deworming of helminth-infected individuals, which as a more pathogenic Th2 subset with enhanced effector functions potentially exert specific regulatory functions [ 43 ]. Their results therefore indicate that, in order to dissect the potentially balancing effects of Th2 versus Th1 responses under TSO therapy, an even more detailed analysis of both subsets would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Some headway has also been made in employing CyTOF to investigate parasites‐induced immune regulatory networks. By profiling type‐2 immune response through a 37‐marker CyTOF analysis, Ruiter et al revealed detailed insights into the spectrum of immunomodulatory effects of helminth infection 148 . Heathy Indonesians, Indonesians infected with soil‐transmitted helminths, and healthy Europeans that are not normally exposed to helminths were profiled.…”
Section: Applicationsmentioning
confidence: 99%